Methodological Basis of Statistical Research on Russia’s Food Security - PANKOVA, Svetlana Valentinovna; TSYPIN, Alexandr Pavlovich; POPOV, Valery Vladimirovich (Journal of Environmental Management and Tourism; Vol 8 No 1 (2017): JEMT Volume VIII Issue 1(17) Spring 2017DO - 10.14505//jemt.v8.1(17).11, 2017)
The article considers theoretical and practical approaches to studying the level of food security in Russia in the context of statistics. The study of the theoretical material enabled to create a terminology database of the “food security” concept, as well as the conceptual framework of the statistical study of Russian food safety. This model is based on the hypothesis made up of three components which are studied to identify statistical relationships: 1) the relationship between food security and inflationary processes; 2) regional differentiation of food security level; 3) consideration of specific features of certain food groups and regional clusters. This algorithm revealed the threat of undermining food security due to the ruble devaluation, falling living standards and a significant reduction in production; substantial differentiation of Russia’s federal subjects by the food security level; the regression models based on panel data showed that there are strong individual effects and the identified relationship should be considered when creating a strategy to increase food security. The paper represents the first attempt to scientifically verify methods of statistical research on the country’s food security. The findings can be used in further research on food safety issues, both by independent researchers and state authorities.